PERBANDINGAN PRESTASI BELAJAR ANTARA SISWA DENGAN ORANGTUA TUNGGAL DAN SISWA DENGAN ORANGTUA UTUH - Nurjaman Hidayatulloh (Psympathic : Jurnal Ilmiah Psikologi, 2011)
This research is done on the students at twelfth grade at MAN Cililin Bandung. The researcher feels interesting to investigate the comparison of study achievement between the students who have single parent and the students who have complete parent. According to the teacher of guidance and counseling, there is a problem in academic achievement for the students who have a single parent. This research uses the study comparison to know the achievement comparison of the students who have single or complete parents. The research uses the quantitative method and uses comparison analysis.  The sample uses non random purposive sampling and simple random sampling. The tool of measurement uses the report score. The result of data analysis shows that pvalue is lower than  α. It means that  Ho  is rejected and H1 is accepted. There is the differences between the students who have single parent and the students who have complete parent.